Behavioral and Environmental Influences on Entrepreneurial Orientation - Chen, Jeff Y-J; Urban, Boris (Journal of Economics and Behavioral Studies, 2018)
Traditionally, theories of innovation and entrepreneurship have concentrated on either environmental or dispositional variables to explain different rates and levels in entrepreneurial activity. However, these theories have unsuccessfully represented the complexity of human behavior actions involve the interaction of various environmental, cognitive, and behavioral variables. Recognizing this shortcoming and considering that contextual influences on entrepreneurial behavior in an emerging market context are rarely accounted for, this study empirically examined the degree to which individual-level variables of entrepreneurial alertness and self-efficacy interact with environmental dynamism and hostility to influence a firm’s entrepreneurial orientation. Appreciating the multiplicity of elements facing an entrepreneur who is trying to make sense of the external environment, the study surveyed 310 owner-mangers in South Africa and relied on SEM to determine the best model fit. The study findings reveal that as a result of mediating and interaction effects, an individual with higher levels of alertness and self-efficacy is more likely to be innovative, engage in risk-taking behavior and show pro-activeness, in other words, have higher levels of entrepreneurial orientation. It is recommended that policymakers encourage entrepreneurial orientation by fostering a high-support route in which the effects of the hostile environments are minimized to encourage higher levels of innovation. Moreover, scholars can build on these findings by investigating the interconnectedness of exogenous environmental and individual factors in terms of explaining entrepreneurial orientation.